Design Evaluation of Air Receiver Tank for Gas Power Plant Using Finite Element Analysis - Kamaludin, Reza; Feriyanto, Dafit (Journal of Advanced Industrial Technology and Application, 2023)
In order to improve the power capacity in Bali, an air receiver tank is required, which is a tank used to store compressed air produced by an air compressor. The design of this air receiver tank aims to analyze the performance of the existing air receiver tank and compare it with the proposed design in this research. The analysis includes the impact of various factors on the design of the air receiver tank regarding its performance. Several components were created during the fabrication process, including the shell, bottom head, top head, and several instruments of the required components with design pressures of 10, 12, and 1.6 MPa. The research process is mapped using three methods: manual calculations based on ASME Section VIII Division I standards, finite element analysis simulation using the SolidWorks application, and hydrostatic testing. The manual calculation results indicate a shell thickness of 7.57868 mm and head top and bottom thicknesses of 7.53 mm, which are capable of accommodating the maximum pressure with MAWP (Maximum Allowable Working Pressure) values of 1.38 MPa for both the shell and head. The design script support calculation yields a result of 0.3 mm. Based on the finite element analysis simulation using the SolidWorks application, the results show that the tank can withstand a load of up to 1.6 MPa, with material stresses at the head top being 90.0 MPa, head bottom at 0.1 MPa, and shell at 15.5 MPa, with a Min-Max value of 192.0 MPa. Hydrostatic testing with variations in time indicates that the tank can handle a pressure of up to 1.6 MPa, as shown by pressure gauge II-III and temperature gauge II and III, maintaining a stable reading of 1.6 MPa and 76°F.